３ｑ２９欠失症候群モデルマウスにおける精神疾患様の行動異常と大脳皮質神経細胞の過活動 - 森, 大輔; 山本, 果奈; 山口, 瞬; 勢力, 薫; 早田, 敦子; 横山, 一剛; 永安, 一樹; 吾郷, 由希夫; 尾崎, 紀夫; 山本, 雅; 松村, 憲佑; 田熊, 一敞; et al. (日本薬理学会年会要旨集, 2020)
The 3q29 microdeletion is a rare recurrent copy number variant (CNV) leading to an increased risk for neurodevelopmental disorders, such as intellectual disability and autism spectrum disorder (ASD), and a >40-fold increased risk for schizophrenia. However, the neurobiological basis for 3q29 deletion syndrome is currently unknown. In order to investigate the biological changes induced by the microdeletion, we generated a mouse model of human 3q29 deletion syndrome by deleting the orthologous region. 3q29 deletion (Df/+) mice showed reduced body and brain weight. Importantly, Df/+ mice showed deficits in social interaction and prepulse inhibition, which are reminiscent of the phenotypes in patients with 3q29 deletion syndrome. By unbiasedly analyzing the whole-brain neural activity, we found that neuronal activity was abnormally activated in a restricted region of the cortex of Df/+ mice. Furthermore, we found that the expression levels of immediate early genes were increased and that the number of parvalbumin positive neurons was decreased in the cortex of Df/+ mice. Our results suggest that Df/+ mice may provide important clues for understanding the disease-causative molecular and cellular pathology of psychiatric disorders.